Characteristics of saline lake shale oil reservoir and its influence on shale oil enrichment in the Qianjiang Formation, Qianjiang Depression, Jianghan Basin, China. (28th January 2021) - Luo, Jing; Wang, Furong; He, Sheng; Sun, Zhongliang; Wu, Shiqiang
Abstract : The enrichment mechanism and process of shale oil are key issues in the studies on shale oil. To date, a variety of methods have been applied to describe the characteristics of typical shale oil reservoirs and reveal the potential influencing factors on marine and freshwater continental shale. However, geological characteristics and influencing mechanism of saline lake shale oil reservoirs remain poorly understood. Here, we report our investigation on the petrological, organic geochemical, and pore structure characteristics of the 10th cyclothem of the third member (Eq3 4 10) of the saline lake–formed Qianjiang Formation in Jianghan Basin using X‐ray fluorescence spectroscopy, X‐ray diffraction, field emission scanning electron microscopy, low‐temperature nitrogen adsorption, and high‐pressure mercury intrusion. The shales of Eq3 4 10 contain high average carbonate contents (45.53%) and clay minerals (20.89%), as well as anisometric glauberite, quartz, feldspar, rock salt, and pyrite. The main lithofacies are dolomitic mudstone, argillaceous dolomite, and calcareous mudstone. The shale samples tested yield total organic carbon (TOC) and S1 + S2 values of 1.94 wt% and 10.46 mg HC/g rock, respectively, and are primarily types II1 and II2 kerogen with thermal maturities between 0.5 and 1.0%. The abundance of organic matter in calcareous mudstone and dolomitic mudstone facies of the Eq3 4 10 shales was relatively high. Inorganic pores are the dominant pore types, including intercrystalline pores within the carbonate and clay minerals, while mesopores and macropores contribute most to the pore volume. Better pore structures exist in argillaceous dolomite and dolomitic mudstone facies, and their characteristics are mainly affected by the compositions of dolomite, clay minerals, and glauberite and, thus, the TOC and oil contents of the shale oil reservoir. Abstract : Inorganic pores (mainly intergranular) and fractures are the main pore types in Eq3 4 10 shale. The cracks and micron‐sized intergranular pores provided by clay minerals and carbonate minerals and dissolved pores formed by dissolution and intercrystalline pores of carbonate minerals contributed to the enrichment of free hydrocarbons, which are favourable spaces for shale oil enrichment.